Constitutionnalisme français. Expérience de la troisième république - Bochkarev, Sergey (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2013)
The aim of the article is to discuss the prominent features of French constitutionalism that were formed in the last quarter of the 19th century. The author underlines the particular importance of the constitutional experience of France and notes that the form of government and the several political institutions established with the proclamation of the Third Republic also exist in general terms at the present time. Further in the text, the author observes that the practice of the state and legal construction of the French Third Republic was in many ways rather distant from constitutional establishments. It is emphasized that in the practical implementation of the Constitution, the Parliament (mainly the Chamber of Deputies) came to play a major role in the system of government and that in turn has been largely responsible for the durability of the basic constitutional and legal institutions of the Third Republic.